Neural tube defect family with recessive trait linked to chromosome 9q21.12-21.31 - DAĞÇINAR, ADNAN; BAYRAKLI, FATİH; SAKAR, MUSTAFA; ZİYAL, MUSTAFA İBRAHİM; ÜNVER, OLCAY; BAYRİ, YAŞAR (SPRINGER, 2015)
Meningomyelocele is one of the most common and socioeconomically, psychologically, and physically debilitating neurodevelopmental diseases. A few chromosomal locus and genes have been identified as responsible for the disease; however, clear evidence still needs to be produced. This study aimed to show evidence of a strong genetic linkage in a novel chromosomal locus in a family with this neural tube defect. We identified a neural tube defect family in eastern Turkey, where two of six offspring had operations due to thoracolumbar meningomyelocele. The parents were of a consanguineous marriage. We collected venous blood from six offspring of the family. Whole genome linkage analysis was performed in all offspring. A theoretical maximum logarithm of an odds score of 3.16 was identified on chromosome 9q21.12-21.31. This result shows a strong genetic linkage to this locus. Our results identified a novel chromosomal locus related to meningomyelocele and provide a base for further investigations toward the discovery of a new causative gene.
Keywords: Meningomyelocele; Neural tube defects; Whole genome linkage analysis; Chromosome; LOD score; IDENTIFICATION; GENETICS